2002
DOI: 10.1126/science.107355
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Glycoprotein Ibα and Its Complex with von Willebrand Factor A1 Domain

Abstract: Transient interactions of platelet-receptor glycoprotein Ibalpha (GpIbalpha) and the plasma protein von Willebrand factor (VWF) reduce platelet velocity at sites of vascular damage and play a role in haemostasis and thrombosis. Here we present structures of the GpIbalpha amino-terminal domain and its complex with the VWF domain A1. In the complex, GpIbalpha wraps around one side of A1, providing two contact areas bridged by an area of solvated charge interaction. The structures explain the effects of gain-of-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
572
4
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 527 publications
(601 citation statements)
references
References 28 publications
18
572
4
7
Order By: Relevance
“…Mutations affecting a leucine-rich domain of GPIX or its amino-and carboxy-terminal flanking regions all give rise to decreased GPIb/IX/V surface expression on platelets, suggesting that these regions are important to ensure the correct assembly and the stability of the complex [21]. The sequences flanking the LRM of GPIbb, GPIX, and GPIba are very similar, these regions showing conserved cysteine residues that form disulfide loops within the polypeptide, as observed in GPIba by crystallography [22]. It has been suggested that GPIX gene mutations affecting cysteine residues [13,14,21] prevent the formation of intramolecular disulfide-loop structures that are critical for the interaction of the polypeptide with the GPIbb subunit.…”
Section: Discussionmentioning
confidence: 83%
“…Mutations affecting a leucine-rich domain of GPIX or its amino-and carboxy-terminal flanking regions all give rise to decreased GPIb/IX/V surface expression on platelets, suggesting that these regions are important to ensure the correct assembly and the stability of the complex [21]. The sequences flanking the LRM of GPIbb, GPIX, and GPIba are very similar, these regions showing conserved cysteine residues that form disulfide loops within the polypeptide, as observed in GPIba by crystallography [22]. It has been suggested that GPIX gene mutations affecting cysteine residues [13,14,21] prevent the formation of intramolecular disulfide-loop structures that are critical for the interaction of the polypeptide with the GPIbb subunit.…”
Section: Discussionmentioning
confidence: 83%
“…A. Based on homology modeling with the structures of the Nogo receptor (He et al, 2003) and glycoprotein Ibα (Huizinga et al, 2002) as outlined in the text. B.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted and experimental structures of the FSHR-ECD N-terminal fragment (residues 1 -241). A. Molecular modeling with the Nogo receptor (He et al, 2003) and glycoprotein Ibα (Huizinga et al, 2002) as templates. B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations